Heating strategies for Li-ion batteries operated from subzero temperatures - Ji, Yan; Wang, Chao Yang (Electrochimica acta, 2013)
Electric vehicles (EVs) suffer from significant driving range loss in subzero temperature environments due to reduced energy and power capability of Li-ion batteries as well as severe battery degradation due to Li plating. Preheating batteries to room temperature is an essential function of an effective battery management system. The present study employs an electrochemical–thermal coupled model to simulate, for the first time, the process of heating Li-ion batteries from subzero temperatures. Three heating strategies are proposed and compared using battery power, namely self-internal heating, convective heating and mutual pulse heating, as well as one strategy (AC heating) using external power. Their advantages and disadvantages are discussed in terms of capacity loss, heating time, system durability, and cost. For heating using battery power, model predictions reveal that Li-ion batteries can be heated from −20°C to 20°C at the expense of only 5% battery capacity loss using mutual pulse heating with high-efficiency dc–dc converter, implying considerable potential for improved driving range of EVs in cold weather conditions. Moreover, the heating time can be reduced to within 2min by increasing cell output power using convective heating and mutual pulse heating. For external power heating, high frequency AC signal with large amplitude is a preferred choice, offering both high heating power and improved battery cycle life.